(untitled) (Research, Society and Development, 2022)
Objective: to analyze the reported cases of sexual violence that occurred in the State of Maranhão within a time frame. Methodology: this is an epidemiological study of the cross-sectional, descriptive, retrospective, mixed approach, warped by the findings available in DataSUS, via Tabnet, recorded through the Information System of Notifiable Diseases (SINAN) for the State of Maranhão, in the years 2015 to 2020. The following variables were used to govern the study: age group, sex (binary), race and degree of kinship or proximity, and years of notification. Results: there was a record of 3142 cases, with the main victims of this grievance being women 93.22%. In addition, children aged 10 to 14 years (36.38%) were highlighted among the findings, as well as cases among the brown race (72.66%), year of notification was 2020 with 24.44% and the prevalence of 633 cases whose rapist was unknown to the victim. Discussion: this violence is, historically, a prevalent aggravating public health state, highlighting the State of Maranhão, being fostered by the undeniable rape culture and impacting directly on the physical, sexual, psychological, patrimonial and economic health of the victims. Conclusion: given the relevance of this theme, the prevalence of cases in the female public (within the binary aspects) was verified in this study, as could be understood the perpetuation of a negative and vicious cycle historically known. Furthermore, there has been an increase in the number of cases reported, indicating the impacts of the use of the notification systems.